Dissociable Functional Networks of the Human Dentate Nucleus. (19th March 2013) - Bernard, Jessica A.; Peltier, Scott J.; Benson, Bryan L.; Wiggins, Jillian Lee; Jaeggi, Susanne M.; Buschkuehl, Martin; Jonides, John; Monk, Christopher S.; Seidler, Rachael D.
Abstract : The cerebellar dentate nucleus has been reported to project to motor and prefrontal cortical regions in nonhuman primates from 2 anatomically distinct areas. However, despite a wealth of human neuroimaging data implicating the cerebellum in motor and cognitive behaviors, evidence of dissociable motor and cognitive networks comprising the human dentate is lacking. To investigate the existence of these 2 networks in the human brain, we used resting-state functional connectivity magnetic resonance imaging. The resting-state fMRI signal was extracted from regions of interest in the dorsal and ventral dentate nucleus. We report a "motor" network involving the dorsal dentate, anterior regions of the cerebellum, and the precentral gyrus, and a "cognitive" network involving the ventral dentate, Crus I, and prefrontal cortex. The existence of these 2 distinct networks supports the notion that cerebellar involvement in cognitive tasks is above and beyond that associated with motor response components.